2016
DOI: 10.1021/acs.iecr.6b03395
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Bench-Scale Parametric Study on CO2 Capture Using a Carbonic Anhydrase Promoted K2CO3 Solvent with Low Temperature Vacuum Stripping

Abstract: A bench-scale unit was fabricated and used to investigate use of carbonic anhydrase (CA) promoted K 2 CO 3 solvent as an option for CO 2 capture from coal-fired power plants. Bench-scale parametric tests were performed at various CA concentrations, solvent flow rates, and reboiler duties. The CO 2 capture efficiency significantly increases, and regeneration energy requirement decreases, with increasing CA concentrations up to 2.5 g/L, with capture performance leveling off at higher enzyme doses (up to 4 g/L). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…C, when 0.5 wt % CA@ fn -Zn/Fe/MS was added to 30 wt % MEA, desorption of the solvent was enhanced to ∼2.9 mM (taken as 100%), which is 2.6 times higher compared to neat 30% MEA. Similar studies were also reported by various researchers; for instance, Alvizo et al have reported the desorption of CA-assisted N -methyldiethanolamine (MDEA) (4.2 M) at 87–100 °C, and Qi et al found that CA-promoted K 2 CO 3 solution helps in stripping at 75–80 °C. It is well-known that the mechanism of the enzymatic reaction is very complex as a result of the involvement of multiple transition states.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…C, when 0.5 wt % CA@ fn -Zn/Fe/MS was added to 30 wt % MEA, desorption of the solvent was enhanced to ∼2.9 mM (taken as 100%), which is 2.6 times higher compared to neat 30% MEA. Similar studies were also reported by various researchers; for instance, Alvizo et al have reported the desorption of CA-assisted N -methyldiethanolamine (MDEA) (4.2 M) at 87–100 °C, and Qi et al found that CA-promoted K 2 CO 3 solution helps in stripping at 75–80 °C. It is well-known that the mechanism of the enzymatic reaction is very complex as a result of the involvement of multiple transition states.…”
Section: Resultssupporting
confidence: 83%
“…Several research groups have used CA for CO 2 capture in basic solutions, such as 30% K 2 CO 3 and 5−10% alkanolamines. 54,55,49,10 The present study shows that the enzyme-supported matrix developed is robust because it could be recycled 15 times without loss in activity and detachment from the matrix. The CO 2 capture by gravimetric experiment (curve d in Figure 2A) and pressuredrop experiment (curve d in Figure 2B) results also confirmed that there is no significant reductive in activity, even after the 15th run.…”
Section: Energy and Fuelsmentioning
confidence: 67%
“…2019, 20, x FOR PEER REVIEW 11 of 13 designing an upscaled process, this enzyme must be kept in the absorption column, to operate at temperatures below its Tm. This can be achieved through protein immobilization in supports, which can then be used in different absorption process operations, including bubble columns [20] and stirred reactors [21,22]. After heating until 94 °C, the protein was analyzed again at 20 °C, and it is possible to observe that, at pH 9 and pH 11, the changes in the CD spectra caused by heating are maintained and, at pH 10, BCA seems to revert to a CD profile similar to the initial one (Figure S1).…”
Section: Characterization Of Aqueous Media and Bcamentioning
confidence: 99%
“…This correlates to the changes in the secondary structure (Figure 2) where it is possible to observe that, under pH 9 and pH 11, the BCA structure changes more significantly due to the decrease in the antiparallel β-sheet In all cases, the T m values were found to be below typical temperatures adopted in large-scale stripping columns used in CO 2 absorption plants (>75 • C) [15], which indicates that, in the event of designing an upscaled process, this enzyme must be kept in the absorption column, to operate at temperatures below its T m . This can be achieved through protein immobilization in supports, which can then be used in different absorption process operations, including bubble columns [20] and stirred reactors [21,22].…”
Section: Characterization Of Aqueous Media and Bcamentioning
confidence: 99%
“…To date, much fewer studies regarding membrane contactors have been conducted for membrane CO 2 desorption compared with membrane CO 2 absorption. Overall, one of the key obstacles that cause this situation is that CO 2 desorption is usually carried out at elevated temperatures, e.g., at 100-120 • C for elevated-pressure desorption or at 70-100 • C for vacuum desorption [7,8]. High temperature and chemical conditions require membrane materials to exhibit excellent characterizes.…”
Section: Introductionmentioning
confidence: 99%